2021
DOI: 10.3390/ijerph18147331
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Identity in Youth Athletes: A Systematic Review of the Literature

Abstract: Athletic identity (AI), the degree of personal connection to sport, is well-described in adult research; however, this social trait has been less studied in younger age groups. This systematic review describes epidemiological characteristics of AI in youth athletes. PubMed, Embase and PsycInfo were searched to identify AI studies involving quantitative athlete identity outcomes and cohorts 22 years and younger. The search strategy was developed for each database using the Boolean method. PRISMA guidelines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 43 publications
0
48
0
4
Order By: Relevance
“…Differences based on race or ethnicity, age, sport type, or sport competition level were not observed. The literature lacks consensus on how these measures relate to athletic identity, though age and athletic identity may positively correlate ( Lamont-Mills and Christensen, 2006 ; Anderson et al, 2009 , 2011 ; Proios et al, 2012 ; Babić et al, 2015 ; Şekeroğlu, 2017 ; Piatt et al, 2018 ; Edison et al, 2021 ; Rae and Jenkins, 2021 ). Furthermore, the population examined was treated at a specialty sports medicine treatment center, possibly explaining the unequal distribution of competition levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differences based on race or ethnicity, age, sport type, or sport competition level were not observed. The literature lacks consensus on how these measures relate to athletic identity, though age and athletic identity may positively correlate ( Lamont-Mills and Christensen, 2006 ; Anderson et al, 2009 , 2011 ; Proios et al, 2012 ; Babić et al, 2015 ; Şekeroğlu, 2017 ; Piatt et al, 2018 ; Edison et al, 2021 ; Rae and Jenkins, 2021 ). Furthermore, the population examined was treated at a specialty sports medicine treatment center, possibly explaining the unequal distribution of competition levels.…”
Section: Discussionmentioning
confidence: 99%
“…In young adults, Lamont-Mills and Christensen (2006) saw no correlations with athletic identity, while Proios et al (2012) observed differences only in the subcategory of how exclusive athletes were to their athletic identity over other identities. Association of athletic identity and race or ethnicity in the youth population is also poorly defined, though Anderson et al and others suggest that Hispanic and minority youths perceive themselves as having lower athletic identity ( Anderson et al, 2009 , 2011 ; Edison et al, 2021 ). Youth athletes appear to conflate athletic identity and personality as they mature ( Von Rosen et al, 2018 ; Newton et al, 2020 ; Edison et al, 2021 ), though athletic identity may begin to decrease with age at the undergraduate level ( Renton et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AIMS evaluates athletes based on three components: social identity (the belief of fulfilling an athlete role), exclusivity (the degree to which identity and self‐worth are derived from the athlete role), and negative affectivity (negative affect from poor performance). 1 , 10 , 12 The total score ranges from 10 to 70 points, with 10 points representing low athletic identity, 40 points representing moderate athletic identity, and 70 points indicating high athletic identity. CAPTSure was completed to assess the severity of PTS symptoms at the time of study participation.…”
Section: Methodsmentioning
confidence: 99%
“… 5 , 8 Furthermore, athletes are less likely to seek help when struggling with mental health challenges due to a complex set of psychosocial barriers, including the emphasis on mental toughness and the stigma and shame associated with help‐seeking behaviors in this population. 9 , 12 , 13 , 14 , 15 , 16…”
Section: Introductionmentioning
confidence: 99%